Entrainment: Transcendental Condition that Affected with Musical - Rizal, Samsul; Wastap, Jaeni B; Saleh, Sukmawati (Pascasarjana ISBI Bandung, 2024)
This research examines the phenomenon of entrainment, which is associated with atmospheric phenomenon in meteorology, and is now also used in a persons psychological and neurological state that leads to a state of brainwave synchronization (neural entrainment). In the most extreme conditions, this neural oscillation process will make a person enter the transcendental phase. This research is examined through a qualitative method by conducting a literature study of a number of studies on the phenomenon of entrainment. The findings obtained by researchers and academics related to entrainment can be a source of evidence for this research. The results of the research conducted found that entrainment can be the most logical explanation to explain a number of transcendental phenomenon associated with traditional or modern music. Entrainment is also a scientific explanation for the phenomenon of being possessed by spirit in a number of traditional arts in Indonesia and entrainment also affects human behavior which can reach the most extreme phase when affected by music to the subconscious level. This article is not sufficient to provide a significant explanation for the phenomenon of trance in some traditional Indonesian arts. More proofs, experiments, and literature studies are needed to strengthen the explanation of the phenomenon scientifically.